Peran ALCO dalam Optimalisasi ALMA pada Perbankan Syariah - Elinda Nur Hasanah; Dino Baggio Listiiyanto; Yani Aguspriyani (Prodi Ekonomi Syariah Universitas Majalengka, 2026)
Abstract: This study investigates the strategic role of the Asset Liability Committee (ALCO) in optimizing Asset Liability Management (ALMA) in Islamic banking. The increasing complexity of asset and liability management, which demands not only financial balance but also compliance with Islamic principles, led to the selection of this topic. This study uses a qualitative approach with a descriptive method through literature review. Annual reports, financial statements, risk management reports, and related scientific literature constitute secondary data. Analysis was conducted using the Miles and Huberman model, as well as content analysis. According to the research results, ALCO functions as a strategic decision-making center that combines the tasks of risk management, finance, financing, and Islamic compliance. In addition, good governance, a sound information system, and data transparency influence ALCO performance. ALCO must balance profitability with Islamic compliance. According to this study, ALMA optimization is highly dependent on the ALCO's strategic, integrative, and normative roles in supporting the stability and sustainability of Islamic banking.